Role of Organizational Citizenship Behavior (OCB), Perception of Justice and Job Satisfaction on Employee Performance - Siti Hidayah; Harnoto Harnoto (Jurnal Dinamika Manajemen)
This study aims to investigate the role of organizational citizenship behavior (OCB) on employee performance through perception of justice and job satisfaction of employees. Sample for the present study consisted of 309 employees working in Baitul Maal Wat Tamwil (BMT) of Central Java. Result of regression analysis indicated that perception of justice was positively and significantly related to job satisfaction and organizational citizenship behavior (OCB), whereas job satisfaction was found to be related positively and significantly with organizational citizenship behavior (OCB). Then, also perception of justice, job satisfaction, and organizational citizenship behavior (OCB) were found to be related positively and significantly with employee performance. Based on these results, it can be interpreted that perception of justice, job satisfaction, and organizational citizenship behavior (OCB) are valuable components of an organization. These components can become important factors to improve employee and organizational performance. Theoretical and practical implications of the result are discussed.